PENGARUH KUALITAS PRODUK DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN COCA-COLA MELALUI BRAND IMAGE SEBAGAI VARIABEL INTERVENING (STUDI PADA KONSUMEN MINUMAN RINGAN BERSODA MEREK COCA-COLA DI KOTA SEMARANG) - Widya Putri Anjani; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2019)
The soft drink industry is one of the potential industries for the country's economy. Tons of soft drinks types that are circulating in the market trigger the existence of competitive competition. This research aims to determine whether the model of this research is acceptable or not. The model of this research is testing the influence of product quality and advertising to purchase decision Coca-Cola’s brand soft drinks through brand image as an intervening variabel. The population in this study were consumers of Coca-Cola soft drinks in the city of Semarang. The research sample of 100 respondens was taken and the sampling technique used was purposive sampling technique, which means that sampling techniques fit certain criteria. Measurement scale using a Likert scale. Data analysis used regression test, correlation test, determination test, significance test, sobel test and mediation test with SPSS version 21 application. Based on the results of this research indicate that product quality has a significant effect on brand image, advertising has a significant effect on brand image, product quality and advertising have a significant effect on brand image, product quality has a significant effect on purchasing decisions, advertising has a significant influence on purchasing decisions, brand image has a significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions through mediating partial brand image, advertising has a significant effect on purchasing decisions through full mediation of brand image. All hypotheses have a significant p < 0.05. This means, the better of the quality product and the created   advertisements, it will form the brand image of the product so the consumers are convinced to decide on purchase.